156 A SIGN IN TIME…; WHAT IMPACT DOES THE INTRODUCTION OF SIGNAGE HAVE FOR DEMENTIA PATIENTS? – A STAFF PERSPECTIVE. (25th October 2022) - Doyle, C; Davis, A; McNally, S
Abstract: Background: Dementia is often seen as a presenting or existing medical condition for older adults attending hospital services. There are over 64, 000 people in Ireland living with dementia. A hospital-wide environmental audit of an acute Irish hospital was completed using the Irish National Audit of Dementia tool. A priority action from this audit was the introduction of new dementia-friendly signage in key patient areas across the hospital, including nurses' stations, toilets and bedrooms. Methods: Random selection was used to distribute staff questionnaires, gathering their perceptions on the effectiveness of this signage. These questionnaires were multiple-choice based. Results: Forty-six questionnaires were completed across 11 wards and from at least 4 different disciplines. Over 70% of staff members noticed the signage prior to survey completion. Twenty-eight percent of staff members felt that patients required less prompting to topographically orientate themselves. Over 75% of staff felt signage helped improve overall orientation by either a small, moderate or significant amount. Over 40% of staff feel their ward is dementia-friendly. Conclusion: The implementation of dementia-friendly signage has had a positive impact on in-patients with dementia, by improving orientation and by promoting independence levels with this group. Dementia-friendliness of the hospital has improved but further exploration in this area is required.